Respuesta :

Step-by-step explanation:

Given equations:

       y  = x² + 3x - 29    ------ (i)

       y  = 2x - 9  ---------------- (ii)

Now to solve this problem, we must determine the value of x and y;

 Equate equations 1 and 2;

       x² + 3x - 29 = 2x - 9

       x² + 3x - 2x - 29 + 9  = 0

       x² + x - 20  = 0

       x² + 5x - 4x - 20  = 0

       x(x + 5 ) - 4(x + 5) = 0

      (x - 4) (x+ 5) = 0

       x  - 4  = 0 or x + 5  = 0

      x  = 4 or x = -5;

So;   solve for y now;

     y = 2x - 9

     input x  = 4 or x = -5;

    y  = 2(4) - 9 or y = 2(-5) - 9

    y = -1 or y = -19